Is the Coarse-Grid Global Climate Model a Useful Tool for Regional Paleoclimate Reconstruction? - Szuman, Izabela; Czernecki, Bartosz (Quaestiones Geographicae, 2011)
This study considers the climate at the time of the Weichselian ice sheet maximum in Central Europe, especially in Poland, in respect of the NASA Educational version of Global Climate Model (EdGCM). The final results of the EdGCM simulations for the Last Glacial Maximum (LGM) are presented here and these have been analysed to determine whether or not they are useful for regional scale modelling; the problem being that, in a global climate model, both horizontal and vertical grid resolution is very low. Also, an attempt has been made to define the role of the ice megalobe which, in terms of the numerical coarse-grid model, covered the northern parts of Germany and Poland. The broad details of the climate during the Weichselian are defined and our results are compared with previous opinion. The influence of ice megalobe on regional climate is demonstrated and it is also concluded that a coarse-grid global climate model could be a helpful tool in a regional climate recognition. However, whether at a regional or local scale, it is recommended that a specially-configured version of a Regional Climate Model (RCM) based on Global Climate Model (GCM) boundary conditions be used in similar reconstructions.